Analisa Yuridis atas Pelaku Tindak Pidana Penggelapan Ditinjau dari Pasal 372 Kitab Undang-Undang Hukum Pidana - Zulkipli; Maman Suparman (Jurnal Hukum dan Demokrasi (JHD), 2025)
Especially regarding embezzlement, which is regulated in chapter XXIV, article 372 to article 377 of the Criminal Code as follows "Anyone who deliberately and illegally belongs to something that is wholly or partly owned by another person, but who is in his power not because of a crime, is threatened with embezzlement. , with a maximum imprisonment of four years or a maximum fine of nine hundred rupiahs ”. The methodology used in this study is a normative juridical legal approach. Normative research or also known as literature law research, is "legal research conducted by examining library materials, both written in the book (law as it is written in the book), as well as the law decided by a judge through a court process. Normative legal research is based on secondary data and emphasizes speculative-theoretical steps and normative-qualitative analysis. Normative legal research is research that uses methods that refer to the legal norms contained in statutory regulations and court decisions related to corruption.,